2011
DOI: 10.1177/0021998311410497
|View full text |Cite
|
Sign up to set email alerts
|

Application of natural fiber composites to musical instrument top plates

Abstract: A flax-reinforced sandwich structure suitable for replacing wood in the top plates of string musical instruments was developed. The mechanical properties of Sitka spruce, the most widely used wood species for this application, were taken as a benchmark when the new materials were developed. The materials were characterized by static and dynamic methods to determine the dynamic Young’s modulus, shear modulus, internal friction, and static mechanical properties. Based on the material characterization, a hand lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…3 Phillips et al made use of unidirectional flax/epoxy hot melt prepregs in a balsa core sandwich structure to achieve similar bending properties to wood species commonly used in the top plates of string musical instruments. 4 In a study by Baets et al on flax yarn twist angle, it was shown that an automated prepregger allows for the use of untwisted yarns that make full use of the mechanical properties of flax fibres. 5 Although the above studies have shown the potential of these materials, little is known on the relationships between uncured prepreg properties, processing parameters and part quality.…”
Section: Introductionmentioning
confidence: 99%
“…3 Phillips et al made use of unidirectional flax/epoxy hot melt prepregs in a balsa core sandwich structure to achieve similar bending properties to wood species commonly used in the top plates of string musical instruments. 4 In a study by Baets et al on flax yarn twist angle, it was shown that an automated prepregger allows for the use of untwisted yarns that make full use of the mechanical properties of flax fibres. 5 Although the above studies have shown the potential of these materials, little is known on the relationships between uncured prepreg properties, processing parameters and part quality.…”
Section: Introductionmentioning
confidence: 99%
“…An advanced knowledge of the dynamical behavior of composite materials is needed for a number of applications, ranging from damage identification [2,3,4,5] to material replacement [6,7] or structural optimization [8,9,10]. More specifically, the non-destructive evaluation (NDE) of the linear viscoelastic dynamical behavior of composite structures is an active research field [11].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their configurability, many manufacturers are investigating the use of composite materials for the manufacture of these instruments. The most common are those using Carbon Fiber Reinforced Epoxy (CFRE) [11,33,34], but others include those involving bio-composites [35,36]. These studies relate the mechanical characteristics of the composite to the sound behavior of different musical instruments, but do not contemplate the direct influence of the processing on the elastic and non-elastic behavior of the vibration.…”
Section: Introductionmentioning
confidence: 99%